Ecological spirituality - Rolston, Holmes, 1932-2025, author; University of Illinois Press, publisher (Colorado State University. Libraries, 1997)
Biology and religion have increasingly joined in recent years in admiration and care for the marvels of natural history. No other species can be either responsible for or religious toward this planet, but Homo sapiens reaches a responsibility that assumes spiritual dimensions. The evolutionary and ecological creativity, and the biodiversity values these generate, are the ground of our being, not just the ground under our feet. We cannot take biology seriously without a respect for life, which often becomes a reverence for life. If anything on Earth is sacred, it must be this enthralling generativity that characterizes our home planet.
Keywords: spirit and nature; respect for life; sacred Earth; biology; religion; natural history; biodiversity; ecological creativity